Effect of Coriander (Coriandrum sativum) Smoke on Physico-Chemical and Sensory Characteristics of Mudaffara Cheese - Jado, Salha A. Y.; Zubeir, Ibtisam El (Food ScienTech Journal, 2023)
This study was done to compare physiochemical and sensory attributes of smoked and non smoked Mudaffara cheese using Coriandrum sativum seed. Mudaffara cheese was prepared from fresh cow's milk and the resulted cheese was divided into two portions; the treated cheese, which was smoked by Coriandrum sativum in a close smoker for about 2 hours. The second portion was left as a control. Both cheeses were packed into labeled plastic containers and stored for five weeks in the refrigerator. The analysis was carried out in the first day, then every week. The result indicated that the smoked Mudaffara cheese was significantly (P<0.05) higher in total solids, protein and fat contents compared to the control cheese, which revealed significantly (P<0.05) higher acidity compared to the smoked Mudaffara cheese. The study also found significant (P<0.05) variations in protein and total solids content and the acidity of Mudaffara cheese during the storage period. The smoked Mudaffara cheese showed higher scores for flavor, salt and overall acceptability as was stated by the panelists, however the better color was recorded for unsmoked Mudaffara cheese. Hence the present study concluded that smoking using Coriandrum sativum seed improve the keeping quality and acceptability of Mudaffara cheese.